Cotinine Enhances Fear Extinction and Astrocyte Survival by Mechanisms Involving the Nicotinic Acetylcholine Receptors Signaling - Oliveros-Matus, Patricia; Perez-Urrutia, Nelson; Alvarez-Ricartes, Nathalie; Echeverria, Florencia; Barreto, George E.; Elliott, James; Iarkov, Alexandre; Echeverria, Valentina (Frontiers in Pharmacology, 2020)
Fear memory extinction (FE) is an important therapeutic goal for Posttraumatic stress disorder (PTSD). Cotinine facilitates FE in rodents, in part due to its inhibitory effect on the amygdala by the glutamatergic projections from the medial prefrontal cortex (mPFC). The cellular and behavioral effects of infusing cotinine into the mPFC on FE, astroglia survival, and the expression of bone morphogenetic proteins (BMP) 2 and 8, were assessed in C57BL/6 conditioned male mice. The role of the alpha4beta2- and alpha7 nicotinic acetylcholine receptors (nAChRs) on cotinine´s actions were also investigated. Cotinine infused into the mPFC enhanced contextual FE and decreased BMP8 expression by a mechanism dependent on the alpha7nAChRs. In addition, cotinine increased BMP2 expression and prevented the loss of GFAP+ astrocytes in a form independent on the alpha7nAChRs but dependent on the alpha4beta2 nAChRs. This evidence suggests that cotinine exerts its effect on FE by modulating nAChRs signaling in the brain.